PENGARUH LINGKUNGAN KERJA TERHADAP MOTIVASI KERJA PADA PT BPR PRISMA DANA MANADO - CHRISTIAN WAROUW; Sontje M. Sumayku; Tinneke M. Tumbel (Universitas Sam Ratulangi, 2017)
The success of an institution or organization is determined by the quality of the componentsand systems in which the components are interconnected, one of which is human resources.To achieve the goals of an organization then what managers need to do is to encourageemployees to work according to what the organization wants. One of them through theprovision of motivation to employees, because with the high work motivation in a person, itwill arise employee morale in the employee who will create a good work productivity. Howworking environment conditions against employee motivation anda how the effects of workenvironment on employee motivation motivation PT BPR. Prisma Dana. This researchincludes quantitative research because the formulation of hypotheses and variabels used istaken from existing theory, tha is work environment theory for insependent variable and workmotivation theory for the dependent variable. Research time is estimated approximately 1month, to obatin the data needed in this study, researchers conductedresearch on PT. BPRPrisma Dana Manado. As for the population in this study are employees of PT. BPR PrismaDana Manado totaling 60 peoples. And i took the sample to be studied amounted to about 30people. Analysis of the data above shows that the work environment has a significant positiveinfluence on the motivation of work PT. BPR Prisma Dana Manado. This is indicated byseveral tests conducted on work environment variabels. Like t test above. In simple correlationanalysis shows that there is a close relationship between work environment with workmotivation. The results of these studies prove an simultaneously answer the hypothesis thatthere is influence between the work environment on employee motivation in PT. BPR PrismaDana Manado. There is a significant influence between work environment on employee workmotivation PT. BPR Prisma Dana Manado. By looking at the average achievement of allworking environment indicators achieved, presumably for all employees of PT. BPR PrismaDana Manado still maintains the achievements that have been obtained.Keywords : Work Environment, Work Motivation